Genome‐wide scan for circulating vascular adhesion protein‐1 levels: MACROD2 as a potential transcriptional regulator of adipogenesis - Chang, Yi‐Cheng; Hee, Siow‐Wey; Lee, Wei‐Jei; Li, Hung‐Yuan; Chang, Tien‐Jyun; Lin, Ming‐Wei; Hung, Yi‐Jen; Lee, I‐Te; Hung, Kuan‐Yi; Assimes, Themistocles; Knowles, Joshua W; Nong, Jiun‐Yi; et al. (Journal of diabetes investigation, 2018)
Aims/Introduction Vascular adhesion protein‐1 (VAP‐1) is a membrane‐bound amine oxidase highly expressed in mature adipocytes and released into the circulation. VAP‐1 has been strongly implicated in several pathological processes, including diabetes, inflammation, hypertension, hepatic steatosis and renal diseases, and is an important disease marker and therapeutic target. Here, we aimed to identify the genetic loci for circulating VAP‐1 levels. Materials and Methods We carried out a genomic‐wide linkage scan for the quantitative trait locus of circulating VAP‐1 levels in 1,100 Han Chinese individuals from 398 families in the Stanford Asian Pacific Program for Hypertension and Insulin Resistance study. Regional association fine mapping was carried out using additional single‐nucleotide polymorphisms. Results The estimated heritability of circulating VAP‐1 levels is high (h2 = 69%). The most significant quantitative trait locus for circulating VAP‐1 was located at 38 cM on chromosome 20, with a maximum empirical logarithm of odds score of 4.11 (P = 6.86 × 10−6) in females. Regional single‐nucleotide polymorphism fine mapping within a 1‐unit support region showed the strongest association signals in the MACRO domain containing 2 (MACROD2) gene in females (P = 5.38 × 10−6). Knockdown of MACROD2 significantly suppressed VAP‐1 expression in human adipocytes, as well as the expression of key adipogenic genes. Furthermore, MACROD2 expression was found to be positively associated with VAP‐1 in human visceral adipose tissue. Conclusion MACROD2 is a potential genetic determinant of serum VAP‐1 levels, probably through transcriptional regulation of adipogenesis. Vascular adhesion protein‐1 (VAP‐1) is a membrane‐bound aminine oxidase that is highly expressed in mature adipocyte and is released into circulating. VAP‐1 has been strongly implicated in several pathological processes and is an important disease marker as well as therapeutic target for pharmaceutical industry. We conducted the first genome‐wide scan for circulating VAP‐1 levels in a large family cohort. We identified MACROD2 is a qualitative trait loci for circulating VAP‐1.